Analysis of theses conducted with mathematics teachers on education of gifted students in Türkiye - Erdoğan, Fatma; Aygün, Pelin Güler (Genç Bilge Yayıncılık, 2025)
Mathematical giftedness refers to an individual’s capacity to easily generalize mathematical knowledge, develop original solution strategies, and interpret the world through a mathematical perspective. The role of teachers is a decisive factor in enabling mathematically gifted students to maximize their potential. Besides, studies on research trends, which are considered the most effective way of defining a field, have gained particular importance in today’s academic landscape. Accordingly, the purpose of this research is to analyze graduate theses indexed in the National Thesis Center of the Council of Higher Education (NTCCHE) that were conducted with mathematics teachers on education of gifted students under eight categories: year, type, paradigm (approach), model, sample type, sample size, data collection tool, and research topic. In this study, a qualitative research approach was adopted, and thematic content analysis (meta-synthesis). The study included theses published between 2009 and 2024. Accordingly, this research was carried out on 17 theses conducted with mathematics teachers in the field of gifted education. The data were collected through document analysis. The findings indicate that the studies were predominantly conducted at the master’s level, employing qualitative and descriptive methods, with a teacher-centered focus and small-scale samples. The theses mainly concentrated on the development of programs, activities, and scales, while student-centered topics were found to be more limited. While this emphasis strengthens the practical orientation of the field, it also highlights the need for greater attention to student-focused dimensions such as creativity, problem-solving, and self-regulation.
Keywords: Special Talented Education; Özel Yetenekli Eğitimi